Sosialisasi Strategi Meningkatkan Literasi Minat Baca melalui Pojok Baca di Desa Gunung Menyan, Kecamatan Pamijahan, Kabupaten Bogor - Musyaropah, Wardatul; Suryani, Ermi; Amalia, Nurul; Sundari, Deva Sri; Mukri, Rusdiono (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2025)
This community service is carried out to grow and develop reading literacy in the general public. With the procurement of a library and the development carried out, it fosters interest in reading in the Mt. Menyan, District. Pamijahan. This service is carried out first by using a descriptive qualitative approach. This service is an attempt to link the research process into the process of social change. The low interest in reading in the community was resolved with a solution for the procurement of a Mini Village Library called the "Reading Corner". The importance of reading is socialized in the form of conducting seminar activities involving expert speakers in the field of reading literacy and writing many scientific works in the form of books, journals and articles. To increase public interest in participating, the event was accompanied by door prizes to participants who were active during the activity. Participants consist of the general public (parents, youth/students and children). These participants were presented to show the importance of each understanding the urgency of literacy and the importance of increasing reading interest. Every individual certainly has experienced obstacles and even problems that can be solved with the writings in the books that have been held in the library. People who create a high reading culture will be able to solve problems positively.